Methods of wintering steer calves that are to be grazed a full season and sold off of grass. - Smith, E.F.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
It is a well known fact that thin steers usually gain more on grass than fleshy steers. However, little information is available about the total gain, winter and summer, of steers wintered in different ways and then grazed on bluestem pasture. The primary objective of this test is to determine how steer calves that are to be grazed a full season on bluestem pasture and sold off grass should be wintered. This is the first years work on a three-year project.
Keywords: Beef; Winter grazing; Bluestem pasture; Gain; Protein